Effect of a nursing program on care focused on the development of the premature newborn - Quispe-Castillo, Marleny (2023)
Objective. To determine the effect of a nursing program on care focused on the development (neurodevelopment) of the premature newborn (RNPT) in the neonatal intensive care service of the National Maternal Perinatal Institute (INMP) 2021. Materials and Methods. Pre-experimental research, application level and quantitative approach, nursing care population of the INMP neonatal intensive care service, sample made up of 26 nurses. The techniques used were observation and survey and two instruments, checklist (KR 0.792) and Likert scale (Crombach's Alpha 0.917), applied in 2 phases before and after the intervention program. The data collected was processed with the SPSS program and the Mc Nemar test was used to measure the effect of the intervention program. The study was authorized by the functional research unit of the National Maternal Perinatal Institute. Results. There is a difference in the care practices focused on the development of the RNPT applied by the nurses of the neonatal intensive care service of the INMP, evidenced by p=0.031 (p<0.05). Before the intervention program the nurses had 73.1% of adequate practices, after the intervention program the adequate practices increased to 96.2% and the inadequate practices decreased from 26.9% to 3.8%. Conclusions. The nursing intervention program on development-focused care in the INMP neonatal intensive care service can improve the effectiveness of RNPT care. Finding in its highest percentage adequate practices after the intervention program.